Music Therapy in Canada: An Interview with Susan Munro-Porchet - Shugar, Bill (Voices: A World Forum for Music Therapy, 2009)
Music has the potential and power to reach, move, disturb, comfort or relax persons beyond their cognitive control and to reach innermost depth. A music therapist therefore needs to tread mindfully, with much respect and an astute awareness of boundaries.